Label-free piezoelectric immunosensor for rapid assay of Escherichia coli - Pohanka, Miroslav; Skládal, Petr; Pavlis, Oto (Journal of immunoassay & immunochemistry, 2008)
A piezoelectric sensor with immobilized polyclonal antibody was developed as a label-free assay for the model bacterium, Escherichia coli. The polyclonal antibody was prepared from mice BALB/c and covalently immobilized on the sensing gold electrode of the piezoelectric quartz crystal. The biosensor was able to detect E. coli in the range of 10(6)-10(9) CFU/mL; signal of the negative control was not statistically relevant in the selected range. Samples could be analyzed in four minutes and one measuring cycle including regeneration was completed within ten minutes. Repeatability of the developed method is discussed; the signal obtained from three different biosensors was 12.9+/-0.4 Hz for the sample containing 10(8) CFU/mL.
Keywords: myši inbrední BALB C; Escherichia coli; Animals; elektrody; Electrodes; Gold; Biosensing Techniques; Mice, Inbred BALB C; zlato; myši; zvířata; křemen; Antibodies, Bacterial; protilátky bakteriální; biosenzitivní techniky; Mice; Quartz